RNA Polymerase III Regulates Cytosolic RNA:DNA Hybrids and Intracellular MicroRNA Expression - Koo, Christine Xing'er (J Biol Chem, 2015)
RNA:DNA hybrids form in the nuclei and mitochondria of cells as transcription-induced R-loops or G-quadruplexes, but exist only in the cytosol of virus-infected cells. Little is known about the existence of RNA:DNA hybrids in the cytosol of virus-free cells, in particular cancer or transformed cells. Here, we show that cytosolic RNA:DNA hybrids are present in various human cell lines, including transformed cells. Inhibition of RNA polymerase III (Pol III), but not DNA polymerase, abrogated cytosolic RNA:DNA hybrids. Cytosolic RNA:DNA hybrids bind to several components of the microRNA (miRNA) machinery-related proteins, including AGO2 and DDX17. Furthermore, we identified miRNAs that are specifically regulated by Pol III, providing a potential link between RNA:DNA hybrids and the miRNA machinery. One of the target genes, exportin-1, is shown to regulate cytosolic RNA:DNA hybrids. Taken together, we reveal previously unknown mechanism by which Pol III regulates the presence of cytosolic RNA:DNA hybrids and miRNA biogenesis in various human cells.